The pallbearers club : a novel - Tremblay, Paul (William Morrow, an imprint of HaperCollinsPublishers, 2022)
"A cleverly voiced psychological thriller about an unforgettable--and unsettling--friendship, with blood-chilling twists, crackling wit, and a thrumming pulse in its veins--from the nationally bestselling author of The Cabin at the End of the World and Survivor Song. What if the coolest girl you've ever met decided to be your friend? Art Barbara was so not cool. He was a seventeen-year-old high school loner in the late 1980s who listened to hair metal, had to wear a monstrous back-brace at night for his scoliosis, and started an extracurricular club for volunteer pallbearers at poorly attended funerals. But his new friend thought the Pallbearers Club was cool. And she brought along her Polaroid camera to take pictures of the corpses. Okay, that part was a little weird. So was her obsessive knowledge of a notorious bit of New England folklore that involved digging up the dead. And there were other strange things--terrifying things--that happened when she was around, usually at night. But she was his friend, so it was okay, right? Decades later, Art tries to make sense of it all by writing The Pallbearers Club: A Memoir. But somehow this friend got her hands on the manuscript and, well, she has some issues with it. And now she's making cuts. Seamlessly blurring the lines between fiction and memory, the supernatural and the mundane, The Pallbearers Club is an immersive, suspenseful portrait of an unusual and disconcerting relationship"--Dust jacket flap.